Pengaruh Kecukupan Modal, Likuiditas, dan Dewan Komisaris Independen Terhadap Profitabilitas Perbankan Syariah di Indonesia - Annisa Putri, Nadia; Zulaihati, Sri; Ketut Agung Ulupui, I Gusti (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The Sharia Economic and Financial Sector has a positive projection of increasing economic growth in Indonesia, namely being able to contribute as much as 13.82% yoy, starting from the Islamic banking sector. This is evidenced by the data from the Financial Services Authority (OJK), which grew from sharia banking to Rp. 680.09 trillion in 2022. However, in the midst of rapid growth, in fact, sharia banking is experiencing instability, fluctuating profitability is the main problem. This study aims to determine the effect of capital adequacy, liquidity, and independent board of commissioners on the profitability of Islamic banking in Indonesia. The research method used is a quantitative method with secondary data obtained from financial reports. Reports on financial ratios and reports on governance of Islamic banking registered with the Financial Services Authority (OJK) with a total sample of 12 Islamic commercial banks in a 5-year study period. The data analysis used was the requirements analysis test, the classical assumption test, the multiple regression equation test, and the hypothesis test. The results of the research partially show that capital adequacy has a significant negative effect, liquidity has a significant positive effect, and an independent board of commissioners has no effect on the profitability of Islamic banking. The independent variable used in this study explains its effect on the profitability of Islamic banking by the remaining 69,3% being influenced by other factors.